Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Kasus pada Rumah Makan Rocket Chicken Sampit) - Rahman, Gajali; Rayuwanto, Rayuwanto (Keizai, 2020)
This study aimed to analyze the influence of service and product quality on customer loyalty and customer satisfaction as mediation. The population of the study was one hundred rocket chicken Sampit customers selected using accidental sampling methods. Analytical model used in this research path analysis. The result showed that 1) service quality of Rocket Chicken Sampit has no effect on customer satisfaction, 2) product quality of rocket chicken Sampit has no effect on customer satisfaction, 3) customer satisfaction of rocket chicken Sampit affects customer loyalty, 4) service quality of rocket chicken Sampit has no effect on customer loyalty, 5) product quality of rocket chicken Sampit effect on customer loyalty.